An alternative maneuver to treat gingival recession - Kina, José Ricardo [UNESP]; Suzuki, Thaís Yumi Umeda [UNESP]; Kina, Eunice Fumico Umeda (My University, 2014)
This article reports a clinical case in which was applied autologous bone graft associated with subepithelial connective tis- sue graft, harvested by gingivectomy procedure with technical modifications to increase gingival graft extension, also to be used as guided tissue regeneration, to treat a single gingival recession. After 1 year and 2 months of follow-up, the cover- age of the recession was 4.0 mm, which corresponded to the gain of attached keratinized gingival tissue. An increase in the gingival tissue thickness was observed, without significant probing depth. The procedures applied to treat this case may be biologically and clinically useful to treat gingival recession.
Keywords: Case report; Connective tissue; Esthetics; Gingival recession